Influence of Calcium and Phosphorous Ratio on Hematology and Muscle Proximate Composition of Hypophthalmichthys molitrix Fingerlings - Arshad, Mahnoor; Fatima, Mahroze; Khizar, Ayesha; Ishtiaq, Haseeba; Ali, Muhammad Adnan; Gulzar, Muhammad Omer (BioScientific Review, 2025)
Background. Calcium (Ca) and phosphorous (P) are essential minerals for fish growth and development, but Ca absorption from water is limited and its presence also influences P absorption. Therefore, dietary Ca and P are vital for fish to perform physiological activities efficiently. Methodology. This study investigated the interactive effect of Ca and P ratio (Ca:P) on muscle proximate composition and hematology of Hypophthalmichthys molitrix fingerlings (average initial weight = 13.7 ± 0.05 g) for 90 days. Calcium lactate and sodium di-phosphate were used as Ca and P sources. A total of 9 isonitrogenous, isolipidic, and isocaloric diets were formulated by combining 3 Ca levels (0%, 1%, and 2%) with three P levels (0%, 1%, and 2%) and fed to fish twice a day at 5% body weight. Results. The results showed that moisture and crude protein content in muscles significantly increased (p<0.05) the interactive effect of Ca and P except fat and ash content (p>0.05). Furthermore, the hematological parameters of fingerlings remained unaffected (p>0.05) by the individual supplementation of Ca. However, P supplementation significantly affected the MCV, MHCH, and PLT count. Moreover, the interactive supplementation of Ca and P did not show a significant effect except HCT and MHCH. Platelets count increased at 1% of Ca and 1% of P supplementation, while the RBC count increased at 2% and 1 to 2% (Ca/P). The remaining blood counts did not show considerable variation upon supplementation of Ca/P at different levels. Conclusion. It was concluded that mineral supplementation showed promising results at 1:2 (Ca/P) level for the optimum performance of H. molitrix.